Discharge criteria, practices, and decision-making in the transition of preterm infants to home - Arwehed, Sofia; Axelin, Anna; Ågren, Johan; Blomqvist Thernström, Ylva (Springer Science and Business Media LLC, 2025)
Background
Early discharge to neonatal home care is common practice for preterm infants in Sweden but the evidence base for assessing infant and parent readiness is limited and there are no nationally defined discharge guidelines or criteria. To investigate potential facilitators and barriers in the transition to home, we examined discharge criteria, pre- and post-discharge practices, and staff decision-making.
Methods
All (n = 36) Swedish units participated in this descriptive mixed method study based on semi-structured interviews with one physician and one registered nurse representing each unit.
Results
Discharge criteria and practices varied, both between and within units. Staff were ambivalent about the timing of discharge and postponed giving discharge-related information to parents. The transition process was staff-driven, with limited parental involvement in care planning, and staff discontinuity delayed discharge. Home care combining telemedicine and home visits, adapted to the needs and preference of the family, was considered effective and appraised. Socially vulnerable families or those with limited language proficiency had restricted access to homecare.
Conclusions
There is a need for improved standardization of, and parental involvement in discharge planning for preterm infants. Earlier transfer of care responsibilities to parents should facilitate transition to home and shorten length of hospital stay.
Impact
Our findings provide insight into facilitators and barriers in preterm infants' transition from hospital to home.Staff were ambivalent about timing of discharge, and criteria and practices varied between and within units depending on local routines and staff preferences.The transition process was staff-driven, with limited parental involvement in care planning, and staff discontinuity caused delay.Home care models combining telemedicine and home visits, adapted to the needs of the family, was described as effective and appraised.Empowering parents by earlier transfer of care responsibilities and involvement in care planning, could facilitate transition to home and reduce length of stay.